2015
DOI: 10.1016/j.ijscr.2014.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Rare complication of ventriculoperitoneal shunt. Early onset of distal catheter migration into scrotum in an adult male: Case report and literature review

Abstract: HighlightsCases of scrotal migration of distal catheter in adults are rare.There have been no reports for scrotal migration in adults at an early onset.Early detection of migration of distal catheter prevents shunt malfunction.Prompt surgical management of catheter repositioning is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 54 publications
1
36
0
1
Order By: Relevance
“…The residual peritoneal cavity volume is linearly correlated with the body surface area (80 ml/m 2 ); pediatric patients have a higher Fig. 1 AP radiograph of the chest and abdomen showed shunt tube in the abdomen which was twisted and kinked in its mid portion and its distal end in the right scrotum tendency to have VPS distal catheter migrate into the scrotum due to patent processus vaginalis and smaller peritoneal cavity [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The residual peritoneal cavity volume is linearly correlated with the body surface area (80 ml/m 2 ); pediatric patients have a higher Fig. 1 AP radiograph of the chest and abdomen showed shunt tube in the abdomen which was twisted and kinked in its mid portion and its distal end in the right scrotum tendency to have VPS distal catheter migrate into the scrotum due to patent processus vaginalis and smaller peritoneal cavity [6].…”
Section: Discussionmentioning
confidence: 99%
“…After placement, however, complications are frequent, especially in children. Shunt migration through a patent processus vaginalis within the scrotal sac is a rare event, with only a few cases reported till date [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. We report a case of scrotal migration of VP shunt in a 1-year-old boy, through patent processus vaginalis, who had a background history of congenital hydrocephalus.…”
Section: Introductionmentioning
confidence: 99%
“…Shahizon et al reported a case of scrotal mass formed by coiling of a fractured end of VPS migrating into the scrotum within the hernia sac 8. Lee et al reported a case of VPS migration into the scrotum of an adult male 9. Singh et al compiled data on total 30 cases where VPS migrated into the inguinal hernia sac.…”
Section: Discussionmentioning
confidence: 99%
“…A fractured end of VP shunt tubing migrating to the scrotum within the hernia sac and coiling to form a scrotal mass has also been reported [2]. Lee et al [3] compiled data on cases where a VP shunt migrated into the inguinal hernia sac. On analysing their data, it was seen that there were 61 such cases in 30 case reports.…”
Section: Discussionmentioning
confidence: 99%